HARMONY OF TAḤSĪN - Nurlinda Sapitri; Adiyono Adiyono (International Journal of Teaching and Learning, 2023)
The purpose of this study was to determine how the student's ability to read the Qur'an after learning tahsin control. This type of research is quantitative research. The population and samples used as the subject of this study were class X F MAN 1 Paser students totaling 30 students. This study used several techniques in data collection, namely, observation, tests, and documentation. Data processing uses validity and reliability test formulas, Product moment, "t" test, and determination test. The results showed a Pearson product-moment correlation with the value of "r" at the 5% and 1% significance levels obtained that the value of rxy = 0.527> 0.374 and 0.478, namely the value of rhitug is greater than the value of rtabel both at the 5% and 1% significance levels, so there is a significant relationship between tahsin control and students' ability to read the Qur'an. Furthermore, simple linear regression analysis Y = 49.262 + 0.593, if tahsin control increases by 1%, the ability to read the student's Al-Qur'an will also increase by 0.593. Based on the results of this study, there is a positive influence between tahsin control and students' ability to read the Qur'an by 59%, the higher the tahsin control is implemented, the higher the ability to read the Qur'an will be.